Desde 1x3+1=1(x+1)(x2−x+1),podemosencontraralgunosa,b,c \in \mathbb{R} tal que \frac{1}{x^3+1}=\frac{a}{x+1}+\frac{bx+c}{x^2-x+1 $$}.
Cálculo simple de A muestra que a =-b = \frac {c} {2} = \frac13, es decir\begin{eqnarray}
\frac{1}{x^3+1}&=&\frac13\cdot\frac{1}{x+1}-\frac13\cdot\frac{x-2}{x^2-x+1}\\
&=&\frac13\cdot\frac{1}{x+1}-\frac16\cdot\frac{2x-1}{x^2-x+1}+\frac12\cdot\frac{1}{x^2-x+1}\\
&=&\frac13\cdot\frac{1}{x+1}-\frac16\cdot\frac{2x-1}{x^2-x+1}+\frac12\cdot\frac{1}{\left(x-\frac12\right)^2+\frac34}.
\end{eqnarray} sigue eso\begin{eqnarray}
F(r)&=&\int_0^r\frac{1}{x^3+1}\,dx=\frac13\ln(1+r)-\frac16\ln(r^2-r+1)+\frac{1}{\sqrt{3}}\arctan\frac{2r-1}{\sqrt{3}}+\frac{1}{\sqrt{3}}\arctan\frac{1}{\sqrt{3}}\\
&=&\frac16\ln\frac{(r+1)^2}{r^2-r+1}+\frac{1}{\sqrt{3}}\arctan\frac{2r-1}{\sqrt{3}}+\frac{\pi}{6\sqrt{3}}\\
&=&\frac16\ln\frac{r^2+2r+1}{r^2-r+1}+\frac{1}{\sqrt{3}}\arctan\frac{2r-1}{\sqrt{3}}+\frac{\pi}{6\sqrt{3}}.
\end{eqnarray} así $ \int_0^\infty\frac{1}{x^3+1}\,dx=\lim_{r\to\infty}F(r) = \frac {\pi} {2\sqrt {3}} + \frac {\pi} {6\sqrt {3}} = \frac {2\pi} {3\sqrt {3}}.